N′-[6-(3,5-Dimethyl-1H-pyrazol-1-yl)-1,2,4,5-tetrazin-3-yl]butanohydrazide - Yan, Qi-Dong (International Union of Crystallography, 2011)
In the title compound, C11H16N8O, the tetrazine and pyrazole rings form a dihedral angle of 48.75 (2)°. In the crystal, N—H⋯O and N—H⋯N hydrogen bonds link the molecules into layers parallel to (101).